Efforts of Lithuanian society in 1987–1990 to recognise Molotov Ribbentropp pact as void - Kašauskienė, Vanda (Genocidas ir rezistencija, 2025)
The transformations and a refreshing publicity have naturally awakened public interest in history, based on a desire to open the pages of the past, previously marked by secrecy, as soon as possible and to get a correct perception of the reality. The people of Lithuania reacted extremely sensitively to the horrific crimes of the Stalinist era. Even more so because for almost 50 years of oppression, Lithuanian history has been grossly politicised by the forcefully imposed dogmas of Marxism–Leninism, the application of historical scientific concepts and the evaluation of individual historical periods by ideologues aided by Moscow. It was particularly important to make public the document that led to the occupation of the Baltic states.